[PP.03.05] ANTIHYPERTENSIVE THERAPY AMONG ELDERLY OUTPATIENTS IN MOSCOW. (September 2017) - Ostapenko, V.; Tkacheva, O.; Runikhina, N.; Kotovskaya, Y.; Sharashkina, N.
Abstract : Objective: The purpose of this study is to evaluate the antihypertensive therapy among > 65 years old outpatients in Moscow. Design and method: The study includes 356 patients 65–93 years old. Average age was 74.8 ± 6.1 years old, 80.4% women, 54.8% of them with higher education and 9% still continue to work. Research was conducted in Moscow polyclinic from November 2014 to May 2015. Anamnesis of arterial hypertension, cardiovascular diseases and antihypertensive therapy was evaluated among 2 groups of seniors: 65–79 years old (n = 277) and > 80 years old (n = 79). Results: Antihypertensive therapy was reported by 91.6% (n = 326) patients. Thirty four percent of the patients (n = 98) received monotherapy. Combination of two-drugs were taken by 36.8% (n = 105) of the patients. Three and four drugs combination were taken by 22.5% (n = 64) and 6.3% (n = 18) of the patients, respectively. The study revealed ACE inhibitors and beta-blockers as most frequent drugs (53.7% and 50.5% of patients, respectively). The distribution of another groups of antihypertensive pills is following: angiotensin receptor blocker - 23.9%, diuretic - 38.6%, calcium channel blocker - 34% patients. Myocardial infarction or heart failure was registered by 24% of the patients under BB therapy. Average consumption of antihypertensive drugs of the patients in the age of 65–79 years old is 1.6 ± 1.2. and 1.8 ± 1.2 in age group of > 80 years old. Patients in the age group of 65 - 79 years old took beta-blockers more often, than patients >80 year old (41.2% vs 38%, p = 0.7). However patients group of 65–79 years old took an ACE inhibitors (40.8% vs 50.6%, p = 0.12) or calcium channel blocker (24.5% vs 36.7%, p = 0.04) rarely, than >80 years old patients. Reception frequency of angiotensin receptor blocker and diuretics were similar among abovementioned groups (respectively, 19.5% vs 17.7%, and 29.6% vs 35.4%). Conclusions: Most hypertensive patients > 65 years old receive combination antihypertensive therapy. Combinations of ACE inhibitors + beta-blockers or ACE inhibitors + diuretic are among the most common.